Peningkatan Perekonomian Masyarakat melalui Pendampingan Pengolahan Rumput Laut KWT Rasa Saling Sayang - Zuhdiyah Matienatul Iemaaniah; Riezka Zuhriatika Rasyda; Yy Wima Riyayanatasya; Abdul Majid Azzuandi; Dinda Marita; Rizki Masyhadani Putra (PRIMA: Journal of Community Empowering and Services, 2025)
Improving the Community's Economy through Seaweed Processing Assistance for KWT Rasa Saling Sayang.  Seaweed is a marine product with great economic potential for communities. It contains antioxidants and beneficial substances. Seaweed is consumed both raw and in processed forms. Besides food, it is used in cosmetics, pharmaceuticals, animal feed, fertilizers, and other products. The Rasa Saling Sayang Women Farmers Group (WFG), a food processing MSME in the Mandalika Special Economic Zone, also cultivates seaweed on Serenting Beach. However, limited processing skills among group members hinder the development of their seaweed business, resulting in a need for training and support in making processed seaweed products. This community service aimed to empower The Rasa Saling Sayang WFG’s members to turn fresh seaweed into higher value, longer lasting foods. The community service included socialization and hands on training on July 17 and 29, 2025, at the Rasa Saling Sayang WFG production house, attended by 20 participants. As a result, the group's skills in making seaweed based foods, such as flour, dodol, and jelly drinks, have increased from 6% before training to 100% after, a 94% improvement